Use of High-Field Intraoperative Magnetic Resonance Imaging to Enhance the Extent of Resection of Enhancing and Nonenhancing Gliomas. Issue 4 (23rd December 2013) - Mohammadi, Alireza Mohammad; Sullivan, T. Barrett; Barnett, Gene H.; Recinos, Violette; Angelov, Lilyana; Kamian, Kambiz; Vogelbaum, Michael A.
ABSTRACT: BACKGROUND: Intraoperative magnetic resonance imaging (IoMRI) is used to improve the extent of resection of brain tumors. Most previous studies evaluating the utility of IoMRI have focused on enhancing tumors. OBJECTIVE: To report our experience with the use of high-field IoMRI (1.5 T) for both enhancing and nonenhancing gliomas. METHODS: An institutional review board–approved retrospective review was performed of 102 consecutive glioma patients (104 surgeries, 2010-2012). Pre-, intra-, and postoperative tumor volumes were assessed. Analysis was performed with the use of volumetric T2 images in 43 nonenhancing and 13 minimally enhancing tumors and with postcontrast volumetric magnetization-prepared rapid gradient-echo images in 48 enhancing tumors. RESULTS: In 58 cases, preoperative imaging showed tumors likely to be amenable to complete resection. Intraoperative electrocorticography was performed in 32 surgeries, and 14 cases resulted in intended subtotal resection of tumors due to involvement of deep functional structures. No further resection (complete resection before IoMRI) was required in 25 surgeries, and IoMRI showed residual tumor in 79 patients. Of these, 25 surgeries did not proceed to further resection (9 due to electrocorticography findings, 14 due to tumor in deep functional areas, and 2 due to surgeon choice). Additional resection that was performed in 54 patients resulted in a final median residual tumor volume of 0.21 mL (0.6%). In 79 patients amenable to complete resection, the intraoperative median residual tumor volume for the T2 group was higher than for the magnetization-prepared rapid gradient-echo group (1.088 mL vs 0.437 mL; P = .049), whereas the postoperative median residual tumor volume was not statistically significantly different between groups. CONCLUSION: IoMRI enhances the extent of resection, particularly for nonenhancing gliomas.